Effect of Maternal and Newborn Care Intervention on Maternal Functioning of Primiparous Mothers - Me Me Thwin; Nyi Nyi Htay; Theingi Mya (KHD-Production, 2023)
Primiparous mother is confronted with many physical and psychosocial changes during the postpartum period which consequently affect her maternal functioning. To deal with these changes positively, the maternal functioning of postpartum mothers should be enhanced by the provision of maternal and newborn care intervention (MNCI). A quasi-experimental research pretest post-test comparison group design was used to study the effect of MNCI on the maternal functioning of primiparous mothers. This study was conducted in Mandalay Central Women’s Hospital, Myanmar. A total of 72 primiparous mothers (control group=36, intervention group=36) were recruited by consecutive sampling. The MNCI was given to the intervention group in the form of direct nursing care, individual and group teaching and demonstration using audio-visual materials and an educational booklet, discussion in “Peer Viber Support Group” and follow-up telephone calls. Baseline assessment was done at antenatal 32nd to 36th weeks to assess postpartum self-care knowledge, maternal newborn care knowledge, and social support. At six weeks postpartum, self-efficacy and maternal functioning of participants were assessed in addition to baseline assessment. Descriptive statistics, paired t-test, independent t-test, and Chi-square test were used to analyze the data. The results showed that maternal functioning was significantly improved in the intervention group than the control group at postpartum six weeks (p < 0.05). The improvement was also found in postpartum self-care knowledge, maternal newborn care knowledge, social support, and postpartum self-efficacy of primiparous mothers at postpartum six weeks (p < 0.001). This study highlighted that the MNCI was effective in enhancing the maternal functioning of the primiparous mothers. Further studies are recommended to determine the effectiveness of the MNCI upon health outcomes of postpartum mothers and babies in hospitals and community settings.